CONCOMITANT USE OF STATINS AND S-(2-BORON-ETHYL)-L-CYSTEINE ARGINASE INHIBITOR TO CORRECT ENDOTOXIN-INDUCED ENDOTHELIAL DYSFUNCTION - Tatiana Denisyuk; Serghei Demchenko; Karen Saroyan (Belgorod National Research University, 2015)
The concomitant use of non-selective S-(2-boron-ethyl)-L-cysteine (BEC) arginase inhibitor with simvastatin, atorvastatin, rosuvastatin and nanoparticulated rosuvastatin on the background of endotoxin-induced disorder modeling by Staphylococcus aureus (strain 13407) injection under the skin - 60 billions of microbial bodies - exhibits an endothelium- and cardio-protective action which is evident as endothelial dysfunction factor (EDF) increase prevention, adrenoreactivity, maintenance of myocardial reserve, and normalization of biochemical markers (total NO, expression of eNOS, C-reactive protein, IL-6, tumor necrosis factor). However, the concomitant therapy has shown no additive action of medications.